Zero and Minimal Fluoroscopic Approaches During Ablation of Supraventricular Tachycardias: A Systematic Review and Meta-Analysis - Debreceni, Dorottya; Janosi, Kristof; Vamos, Mate; Komocsi, Andras; Simor, Tamas; Kupo, Peter (Frontiers in Cardiovascular Medicine, 2022)
Introduction Catheter ablations for cardiac arrhythmias are conventionally performed under fluoroscopic guidance. To guide these procedures, zero/minimal fluoroscopy (Z/MF) approaches have become available, using three-dimensional electroanatomical mapping systems. Our aim was to conduct a meta-analysis comparing these two different methods for the treatment of paroxysmal supraventricular tachycardia (SVT). Methods Electronic databases were searched and systematically reviewed for studies comparing procedural parameters and outcomes of conventional, fluoroscopy-guided vs. Z/MF approaches in patients undergoing electrophysiology (EP) procedures for SVTs. The random-effects model was used to derive mean difference (MD) and risk ratios (RRs) with 95% confidence interval (CI). Results Twenty-four studies involving 9,074 patients met our inclusion criteria. There was no difference between the groups in terms of acute success rate (RR = 1.00, 95% CI, 0.99–1.01; p = 0.97) and long-term success rate (RR: 1.01, 95% CI, 1.00–1.03; p = 0.13). Compared to the conventional method, zero-and-minimal fluoroscopy (Z/MF) ablation significantly reduced fluoroscopic time [MD: −1.58 min (95% CI, −2.21 to −0.96 min; p < 0.01)] and ablation time [MD: −25.23 s (95% CI: −42.04 to −8.43 s; p < 0.01)]. No difference could be detected between the two groups in terms of the procedure time [MD: 3.06 min (95% CI: −0.97 to 7.08; p = 0.14)] and the number of ablation applications [MD: 0.13 (95% CI: −0.86 to 1.11; p = 0.80)]. The complication rate was 1.59% in the entire study population and did not differ among the groups (RR: 0.68, 95% CI: 0.45–1.05; p = 0.08). Conclusions The Z/MF approach for the catheter ablation of SVTs is a feasible method that reduces radiation exposure and ablation time without compromising the acute and long-term success or complication rates.